Visual Methodology in Migration Studies - Nikielska-Sekula, Karolina; Desille, Amandine (Springer Open, 2021)
This open access book explores the use of visual methods in migration studies through a combination of theoretical analyses and empirical studies. The first section looks at how various visual methods, including photography, film, and mental maps, may be used to analyse the spatial presence of migrants. The second section addresses the processual building of narratives around migration, thereby using formats such as film and visual essay, and reflecting upon the ways they become carriers and mediators of both story and theory within the subject of migration. Section three focuses on vulnerable communities and discusses how visual methods can empower these communities, thereby also focusing on the theoretical and ethical implications of migration. The fourth section addresses the issue of migrant representation in visual discourses. The fifth and concluding section comprises of a single methodological chapter which systematizes the use of visual methods in migration studies across disciplines, with regard to their empirical, theoretical, and ethical implications. Multidisciplinary in character, this book is an interesting read for students and migration scholars who engage with visual methods, as well as practitioners, journalists, filmmakers, photographers, curators of exhibitions who engage with a topic of migration visually.